2013
DOI: 10.1088/1475-7516/2013/05/026
|View full text |Cite
|
Sign up to set email alerts
|

BINGO: a code for the efficient computation of the scalar bi-spectrum

Abstract: We present a new and accurate Fortran code, the BI-spectra and Non-Gaussianity Operator (BINGO), for the efficient numerical computation of the scalar bi-spectrum and the non-Gaussianity parameter f NL in single field inflationary models involving the canonical scalar field. The code can calculate all the different contributions to the bi-spectrum and the parameter f NL for an arbitrary triangular configuration of the wavevectors. Focusing firstly on the equilateral limit, we illustrate the accuracy of BINGO b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(186 citation statements)
references
References 147 publications
3
183
0
Order By: Relevance
“…ground and the perturbation equations using BINGO [20] without any approximations. We search for the best fit in the vicinity of the ζ ∼ 1.2 (to generate a Tanh step like scalar PPS) and ζ ∼ 2 (to generate a broken scalar PPS) using Powell's BOBYQA minimization algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ground and the perturbation equations using BINGO [20] without any approximations. We search for the best fit in the vicinity of the ζ ∼ 1.2 (to generate a Tanh step like scalar PPS) and ζ ∼ 2 (to generate a broken scalar PPS) using Powell's BOBYQA minimization algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…However this model is interesting, since it is able to provide a balance between Planck low-ℓ suppression and BICEP2 B-mode data. For the evaluation of background and perturbation equations for the potential we have used the publicly available code BINGO [20]. The potential that we are using from [5] is very similar to [12] in the limit ζ = 1.…”
Section: Formalismmentioning
confidence: 99%
“…We have introduced a cut-off of the form exp [−κ k/(a H)] and have worked with κ = 0.1, which is known to lead to consistent results [25,38]. We should mention here that we have made the latest version of BINGO publicly available at the URL: http://www.physics.iitm.ac.in/~sriram/bingo/bingo.html.…”
Section: F Nl For An Arbitrary Triangular Configuration Of the Wavenumentioning
confidence: 99%
“…where is the imaginary part and we evaluate the integral from τ 0 to τ e , where τ e is some time sufficiently long after the Hubble crossing horizon, when the modes are frozen [14,15,34,36,37]. It is common to study non-Gaussianity using the parameter f NL defined by…”
Section: Calculation Of the Bispectrummentioning
confidence: 99%
“…If the perturbations followed a perfectly Gaussian distribution the two points correlation function would be enough, but even the most recent observations are compatible with some non-Gaussianity corresponding to f local NL = 2.5 ± 5.7 and f equil NL = −16 ± 70 [8,11], motivating the theoretical study of the conditions which could have generated it. Some recent developments in the study of models which could generate non-Gaussianity and in the detection can be found for example in [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%